2007
DOI: 10.1177/2156759x0701000308
|View full text |Cite
|
Sign up to set email alerts
|

Helping Rural Adolescents Make Successful Postsecondary Transitions: A Longitudinal Study

Abstract: The longitudinal study in this article tested whether advantages in the career development of high school seniors resulted in better transition outcomes for these young adults 3 years after they graduated from high school. Enhanced career development in high school was significantly connected to more successful transitions into the adult roles of worker and learner and to greater satisfaction with one's life. Providing consistent and competent career development services to all students in high school is an es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Students can learn about their mentor's chosen profession, and build self-esteem and confidence in a supportive environment (Single and Single 2005). e-Mentoring can be an eye-opening experience for rural students and prompts them to consider possibilities that have been outside of their personal experience (Lapan et al 2007). It also is more permanent than a conversation, whether face-to-face or over the telephone, so that students can refer to conversations at a later time (Bennett et al 1998).…”
Section: E-mentoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Students can learn about their mentor's chosen profession, and build self-esteem and confidence in a supportive environment (Single and Single 2005). e-Mentoring can be an eye-opening experience for rural students and prompts them to consider possibilities that have been outside of their personal experience (Lapan et al 2007). It also is more permanent than a conversation, whether face-to-face or over the telephone, so that students can refer to conversations at a later time (Bennett et al 1998).…”
Section: E-mentoringmentioning
confidence: 99%
“…When students are given career development skills in secondary school, there is a significant difference in career aspiration after graduation, and these students often realize advantages (e.g. more satisfied about their career) in young adulthood (Lapan et al 2007). Like in high school, career awareness is important in the middle grades because students must decide which courses to take in high school, and these decisions can affect eligibility for university programs (Osborne and Reardon 2006).…”
Section: E-mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…In the midst of these swirling developmental challenges and often competing educational and social demands, some scholars have suggested that academic, psychosocial, and career counseling can no longer remain separate domains (Lapan, Aoyagi, & Kayson, 2007). But Corbett argues in his article in this issue that school counseling has become a "high stakes, nervous, instrumental orientation" toward taking the "right" courses, scoring high on the SAT, and making the "best" college and career decisions by the age of 18.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies indicate that juveniles' unmet educational needs and their unsuccessful re-integration into the educational system often have a long-term negative impact on their lives which make them more vulnerable for further failures in securing employment which often resulting in economic and social hardship such as poverty, homelessness and recidivism into the juvenile and adult justice systems during their transition from adolescence to adulthood (Coalition for Juvenile Justice, 2001;Altschuler and Brash, 2004;Spencer and Jones-Walker, 2004;Agnew, 2005;Osgood et al, 2005;Snyder and Sickmund, 2006;Lapan et al, 2007;Simoes et al, 2008;Lee and Villagrana, 2015) Since education has profound implications on the juveniles' future and determining the risk of their recidivism, therefore, it is imperative for the juvenile justice systems to improve the re-integration supports and educational programming in the institutions since the previous studies found that juvenile offenders received low quality education and lack of re-integration supports during their confinement and transition into the community (Yohalem and Pittman, 2001;Matvya et al, 2006;Mazzotti and Higgins, 2006;Nellis and Wayman, 2009;Blomberg et al, 2011).…”
Section: Introductionmentioning
confidence: 99%